Irish Travellers : racism and the politics of culture - Helleiner, Jane Leslie, 1961- (Anthropological horizons., 2000)
"The Travelling People constitute a Gypsy-like minority population in Ireland that has been a long-standing target of racism and assimilative state settlement policies. Using archival and ethnographic research, Jane Helleiner's study documents anti-Traveller racism in Ireland and explores the ongoing realities of Traveller life. Through analyses of constructions of Traveller origins, local government records, the provincial press, and debates of the Irish parliament, a history of local and national anti-Traveller discourse and practice in the independent Irish state is revealed and linked to the legitimation and reproduction of other social inequalities, including those of class, gender, and generation. Helleiner's research, conducted in the course of long-term residence in a Traveller camp, supports her historical analysis with an examination of how travelling, work, gender, and childhood become sites for the production and reproduction of contemporary Traveller collective Identity and culture even as they are shaped by oppressive forces of racism. These phenomena are located within political struggles at local, national, and European levels."--Jacket